2018
DOI: 10.1055/s-0037-1615822
|View full text |Cite
|
Sign up to set email alerts
|

Have the Annual Trends of Total Knee Arthroplasty in Rheumatoid Arthritis Patients Changed?

Abstract: As the use of disease modifying antirheumatic drugs have increased, it remains unclear whether or not this has affected the rates of total knee arthroplasty (TKA) in rheumatoid arthritis (RA) patients. Therefore, the purpose of this study was to evaluate the annual trends of RA patients who underwent TKA. Specifically, we evaluated: (1) the annual trends of TKAs due to RA in the United States population; and (2) the annual trends in the proportion of TKAs due to RA in the United States. The Nationwide Inpatien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…In parallel with the raising percentage of patients treated with bDMARDs, which reportedly reached 29.5% in 2018, the remission rate based on DAS28 reached 55.9% in 2018 3 . Contrary to the study based on the Japanese database, a study using the Nationwide Inpatient Sample data from the United States showed a significant increase in TKA performed in RA patients from 2002 to 2013 although the ratio of RA to all primary diseases requiring TKA showed a steady trend 25 . Another trend study using the Nationwide Inpatient Sample data from the United States reported that the prevalence of total elbow arthroplasty and total shoulder arthroplasty in RA patients decreased by 50% and 18%, respectively, from 2002 to 2012 26 .…”
Section: Discussionmentioning
confidence: 61%
“…In parallel with the raising percentage of patients treated with bDMARDs, which reportedly reached 29.5% in 2018, the remission rate based on DAS28 reached 55.9% in 2018 3 . Contrary to the study based on the Japanese database, a study using the Nationwide Inpatient Sample data from the United States showed a significant increase in TKA performed in RA patients from 2002 to 2013 although the ratio of RA to all primary diseases requiring TKA showed a steady trend 25 . Another trend study using the Nationwide Inpatient Sample data from the United States reported that the prevalence of total elbow arthroplasty and total shoulder arthroplasty in RA patients decreased by 50% and 18%, respectively, from 2002 to 2012 26 .…”
Section: Discussionmentioning
confidence: 61%
“…Many authors declare such a percentage as underutilization of UKA, which in turn contributes to the higher reported UKA revision rates [9, 15]. Candidacy studies with high reported UKA candidacy do not take into account patients with rheumatoid arthritis, which is a contraindication for UKA, but is present in the daily practice [10, 17]. Even if patients with rheumatoid arthritis were to be excluded, the candidacy for UKA according to AUC criteria would increase in this study by 0.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with previous arthroplasty were excluded. Patients with inflammatory arthritis and with post-traumatic arthritis were not excluded, due to their presence in the daily practice of surgeons managing knee OA [ 10 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Зокрема, у США щороку виконують близько 500 тис. первинних ендопротезувань колінного суглоба [1] та 22 тис. ревізійних, що потребує значних фінансових витрат [2].…”
Section: вступunclassified